3D FEA modelling of laminated composites in bending and their failure mechanisms. (January 2015) - Meng, M.; Le, H.R.; Rizvi, M.J.; Grove, S.M.
Abstract: This paper developed three-dimensional (3D) Finite Element Analysis (FEA) to investigate the effect of fibre lay-up on the initiation of failure of laminated composites in bending. Tsai-Hill failure criterion was applied to identify the critical areas of failure in composite laminates. In accordance with the 3D FEA, unidirectional ([0]16 ), cross-ply ([0/90]4s ) and angle-ply ([±45]4s ) laminates made up of pre-preg Carbon Fibre Reinforced Plastics (CFRP) composites were manufactured and tested under three-point bending. The basic principles of Classical Laminate Theory (CLT) were extended to three-dimension, and the analytical solution was critically compared with the FEA results. The 3D FEA results revealed significant transverse normal stresses in the cross-ply laminate and in-plane shear stress in the angle-ply laminate near free edge regions which are overlooked by conventional laminate model. The microscopic images showed that these free edge effects were the main reason for stiffness reduction observed in the bending tests. The study illustrated the significant effects of fibre lay-up on the flexural failure mechanisms in composite laminates which lead to some suggestions to improve the design of composite laminates.